Nabī Yūshaʿ: A Sacred Site in Palestine - Friedman, Yaron (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2023)
This article reviews the religious and historical background of Nabī yūshaʿ, a holy site for the Shīʿa located in east Galilee, Israel. The mausoleum of Nabī yūshaʿ located in the Naftali mountains in the upper Galilee was founded by the Shīʿī leadership of Jabal ʿĀmil (south Lebanon). The aim of this paper is to explain the special bond of the Shīʿīs in Lebanon to the figure of Joshua (in Arabic: Yūshaʿ) and to this site. The article offers a first-of-a-kind study of both Shīʿī Lebanese literature and the inscriptions in Arabic that are located at the site.